Omaha, Neb., Rev. Ordinances ch. 28, § 6 (1872) - (:unkn) unknown (My University, 1872)
If any person shall carry any concealed weapon or weapons, or have concealed upon or about his or her person any revolver, pistol, slung shot, bowie knife, or other deadly weapon or instrument, such person shall be deemed guilty of a misdemeanor, and, on conviction thereof, shall be fined in any sum not exceeding twenty dollars.
Keywords: CARRY - CONCEALED